2022
DOI: 10.7554/elife.71877
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous brain, brainstem, and spinal cord pharmacological-fMRI reveals involvement of an endogenous opioid network in attentional analgesia

Abstract: Pain perception is decreased by shifting attentional focus away from a threatening event. This attentional analgesia engages parallel descending control pathways from anterior cingulate (ACC) to locus coeruleus, and ACC to periaqueductal grey (PAG) - rostral ventromedial medulla (RVM), indicating possible roles for noradrenergic or opioidergic neuromodulators. To determine which pathway modulates nociceptive activity in humans we used simultaneous whole brain-spinal cord pharmacological-fMRI (N=39) across thre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(65 citation statements)
references
References 97 publications
2
59
0
Order By: Relevance
“…In order to validate the EPI-based automation approach, we obtained an externally acquired corticospinal GE-EPI dataset consisting of 113 EPI z-shim reference scans acquired on a different MR-system (Oliva et al 2022), which also allowed us to investigate the generalizability of the EPI-based automated approach in a dataset in which the manual selection was conducted by a different researcher (VO). Using this independently acquired data set, we observed that – compared to no z-shim – manual z-shimming resulted in a significant increase in mean signal intensity (t (112) = 19.24, p < .001, difference of 22.1%, CI: 19.7-24.4%) and a significant decrease in signal intensity variation across slices (t (112) = 8.83, p < .001, difference of 37.1%, CI: 29.7- 43.9%).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In order to validate the EPI-based automation approach, we obtained an externally acquired corticospinal GE-EPI dataset consisting of 113 EPI z-shim reference scans acquired on a different MR-system (Oliva et al 2022), which also allowed us to investigate the generalizability of the EPI-based automated approach in a dataset in which the manual selection was conducted by a different researcher (VO). Using this independently acquired data set, we observed that – compared to no z-shim – manual z-shimming resulted in a significant increase in mean signal intensity (t (112) = 19.24, p < .001, difference of 22.1%, CI: 19.7-24.4%) and a significant decrease in signal intensity variation across slices (t (112) = 8.83, p < .001, difference of 37.1%, CI: 29.7- 43.9%).…”
Section: Resultsmentioning
confidence: 99%
“…These data were acquired by VO, RHD, and JCWB as part of a larger project on pharmacological aspects of cortico-spinal pain modulation (Oliva et al, 2022). Here, we report results based on analyzing the z-shim reference data from 117 acquisitions (39 participants, each with three visits).…”
Section: Validation Of Epi-based Automation Approachmentioning
confidence: 99%
See 3 more Smart Citations